Efektivitas Pembelajaran Mendalam DalamPenguasaan Kosa Kata Bahasa Indonesia Di Sekolah - Nisa Puspita (Jurnal Sultra Elementary School, 2025)
This study aims to analyze the effectiveness of implementing deep learning in improving Indonesian vocabulary mastery among elementary school students. Vocabulary is a fundamental component of language acquisition, serving as the foundation for communication, reading, writing, and critical thinking skills. In practice, many elementary students still struggle to master vocabulary due to the dominance of rote learning methods that emphasize memorization rather than comprehension. The lack of contextual and meaningful learning experiences causes students to become less motivated and passive in Indonesian language lessons. To address this problem, the research employed a systematic literature review method by analyzing 15 national journal articles relevant to deep learning strategies and vocabulary mastery. The analysis involved identifying objectives, methodologies, results, and conclusions from each study, followed by thematic synthesis to obtain a comprehensive understanding of the effectiveness of deep learning. The findings reveal that deep learning significantly enhances students’ vocabulary retention, reflective thinking, and the connection between word meanings and real-life experiences. The application of visual media such as illustrated word cards, learning videos, and slot boards helps students concretely associate symbols with meanings. Meanwhile, audio media and collaborative activities encourage students to actively speak, listen, and use words in meaningful contexts. Teachers play a crucial role as facilitators, guiding students through reflective and exploratory learning processes that promote deeper understanding. Moreover, deep learning aligns with the principles of the Merdeka Curriculum, emphasizing contextual, student-centered, and reflective learning. Therefore, the implementation of deep learning can be considered an effective pedagogical approach to improving Indonesian vocabulary mastery in elementary schools while fostering literacy, critical thinking, and communication competence among young learners